Death Aesthetization in Contemporary Artistic Practices - Lousa, Teresa (Arte, Individuo y Sociedad, 2016)
Starting from the famous and enigmatic quotation of the Aristotle’s Poetics, who argues that the human has a natural desire and pleasure to see corpses if mediated by art, is intended to show the relationship between the attraction for the horror and some contemporary art practices surrounding the depiction of death, particularly with regard to the ultimate use of the human corpse as an artistic resource. Avoiding any kind of ethical approach or questioning of the limits of the artistic production, is meant to highlight the phenomenon through the examples brought out by the work of some contemporary artists such as Andy Warhol, Eric Fischl, Damien Hirst, Von Hagens, Andres Serrano, Joel-Peter Witkin and Teresa Margolles: From those who use the corpse in and turn it in something aesthetically pleasant, to others who turn human corpses in sculptures of scientific value, and further other kind of artists who assume the morbid and dramatic life of the corpse in their art production as something structural.